Enabling Stable Zn Anode via a Facile Alloying Strategy and 3D Foam Structure. Issue 7 (24th February 2021) - Fan, Xiaoyong; Yang, Huan; Wang, Xinxin; Han, Jiaxing; Wu, Yan; Gou, Lei; Li, Dong‐Lin; Ding, Yuan‐Li
Abstract: Aqueous zinc‐ion battery (AZIB) has become a promising candidate in grid energy storage due to its low cost, environmental friendliness, and high safety. However, AZIB usually suffers from uncontrollable zinc deposition and dendrite growth as well as hydrogen evolution and passivation on the surface of zinc anode. To address the above issues, a unique 3D Zn alloy foam anode built from Zn–Sn–Pb alloy in 3D Cu foam is constructed by a facile hot dipping method. The proposed 3D Zn alloy anode, through introducing elements Sn and Pb, enhances the hydrogen evolution overpotential, reduces the corrosion current, greatly mitigates the self‐corrosion in the electrolyte, and efficiently inhibits the growth of Zn dendrite during cycling. Importantly, such Zn alloy engineering together with a 3D Cu foam current collector enables highly stable Zn storage properties. The full cell assembled using the proposed 3D Zn alloy anode and MnO2 nanosheet cathode exhibits superior reversible capacity (103.4 mAh g −1 ) and excellent cycling stability (capacity retention of 87% over 4000 cycles) at 1.8 A g −1 . Abstract : A facile alloying strategy and 3D foam structure are developed to synergistically construct stable Zn anode for aqueous Zn‐ion batteries. Such a 3D Zn alloy anode delivers superior cyclability both in symmetric and full cells through greatly mitigating self‐corrosion of Zn anode, and simultaneously inhibiting the growth of Zn dendrite, showing a great potential for practical applications of Zn‐ion batteries.